Users Satisfactions Measurement and Evaluation at the Academic Libraries - Mokhtar, Wan Nor Haliza Wan; Noordin, Siti Arpah; Hashim, Dang Merduwati; Shaifuddin, Norshila (Journal of Informatics and Mathematical Sciences, 2017)
The paper aims to get the real scenario of measurement and evaluation practices in Malaysian Academic Libraries. The scope is on the users’ satisfactions towards the services provided by the academic libraries in Malaysia. This is meant to fulfill the needs and expectations of the academic libraries’ users. The study, which focusing on the measurement and evaluation practices of users’ needs and expectations in Malaysian academic libraries highlights how libraries establish their measurement and evaluation exercises. It includes the perspectives of librarians who directly involved in measurement and evaluation activities in the academic libraries. It may serve a baseline in a general sense for academic libraries of all sizes that could leverage the ideas of fulfilling the needs and expectations of the users.